Size of Vertebral Artery Dissection, Not Location, as a Driver of Concomitant Stroke. (16th November 2020) - Prasad, Nikil; Azad, Hooman; Mitra, Akash; Shlobin, Nathan A; Hopkins, Benjamin; Cloney, Michael; Dahdaleh, Nader S
Abstract: INTRODUCTION: Vertebral artery dissections (VADs) are rare events that occasionally cause ischemic strokes, which can result in severe injury or death in otherwise healthy individuals. VADs can be classified by segment affected or location with respect to the dura (intracranial vs. extracranial). Some VADs are solely intracranial (iVAD) or solely extracranial (eVAD), while others cross the dura (eiVAD). Prior literature has shown that intracranial involvement of a VAD is a predictive factor for stroke. METHODS: Demographic and clinical data on consecutive patients treated at our institution were collected. The modified Rankin Scale (mRS) was used as a metric of neurologic status. Parametric data were compared using Wilcoxon-sum rank tests and non-parametric data were compared using chi-square tests. RESULTS: Patients with eiVADs were more likely to be older (47.84 vs. 42.1, P  = .001) and were more often female than those with eVADs (and P = . 02). Patients with eiVADs were more likely to present with occlusion on initial imaging and have a concomitant stroke at presentation compared to eVADs ( P < . 001, P < . 001) and iVADs ( P < . 001, P < . 001) respectively. Patients with eiVADS were less likely to present with pseudoaneurysm or aneurysm compared to eVADs and iVADs ( P  = .007, P < . 001). eiVADs were more likely to be larger than eVADs or iVADs ( P < . 001, P < . 001). VADs affecting V2 were associated with fracture and vertebral artery occlusion ( P < . 001, P < . 0001). VADs with an intracranial component were more likely to occur in those who were older ( P < . 001) and had a higher CCI ( P  = .014). CONCLUSION: This study makes several key new contributions. It suggests that the size of the VAD is more closely associated with the risk of vertebral artery occlusion and stroke at presentation, rather than intracranial location of the dissection. Second, VADs affecting V2 are more likely to present with an associated fracture. Third, VADs affecting intracranial segments are likely to arise in those who are older and have increased comorbidities.